Omission: Common Simple Present Tense Errors in Students' Writing of Descriptive Text - Masruddin Masruddin (Ethical Lingua: Journal of Language Teaching and Literature, 2019)
This research is aimed to determine and to describe the errors in using simple present tenses in writing descriptive texts made by students, especially in the class D of sixth semester of English Education Department at IAIN Palopo. The data were obtained by conducting a test and using a checklist. Then, the writing products were analyzed using Surface Strategy Taxonomy by Dulay (1982). The result of this research was presented descriptively. From the result, the omission errors were found as the highest of occurrence, which was about 47,05% which revealed that in the class D of sixth semester in English Education Department at IAIN Palopo, still made errors in using simple present tense in writing descriptive text. The errors that are mostly made by students were errors of omission. It is in line with Dulay (1982) which stated that errors of omission are found in greater abundance during the early stages of second language acquisition.